2007
DOI: 10.1080/02680510601100150
|View full text |Cite
|
Sign up to set email alerts
|

New approaches, new vision: capturing teacher experiences in a brave new online world

Abstract: The paper is an exploration of how a group of tutors involved in a major e-learning project reacted to developing and teaching in this environment for this first time. All were experienced face-to-face teachers but had different levels of experience in using technology. Our aim was to capture their individual views on working in an online environment. The import of this cannot be under-estimated, as different views on learning influence the role and potential of technology in an e-learning environment.As the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…This situation was further exacerbated by the 'top down' approach and lack of engagement of all staff at the start of the project. These findings supported findings from Connolly, Jones, and Jones (2007) who undertook a qualitative study exploring how a group of tutors involved in a major e-learning project reacted to developing and teaching in this new environment. In this study, it was found that all respondents were keen to keep an element of face-to-face teaching in their modules and felt it was difficult to gauge the depth of learning of their students without this.…”
supporting
confidence: 51%
“…This situation was further exacerbated by the 'top down' approach and lack of engagement of all staff at the start of the project. These findings supported findings from Connolly, Jones, and Jones (2007) who undertook a qualitative study exploring how a group of tutors involved in a major e-learning project reacted to developing and teaching in this new environment. In this study, it was found that all respondents were keen to keep an element of face-to-face teaching in their modules and felt it was difficult to gauge the depth of learning of their students without this.…”
supporting
confidence: 51%
“…and pedagogy, may be quite challenging for the lecturer. Materials and approaches that work well in a classroom environment may not be effectively replicated online (Connolly, Jones, and Jones 2007). New teaching methods, both in the classroom and in online environments, may also be resisted by students, because they are forced to adopt new study methods.…”
Section: Teacher Reflectionmentioning
confidence: 94%
“…6 Yet if educators embrace tools such as Second Life, Facebook, wikis, and YouTube, student collaboration occurs, which promotes a self-and team teaching effect 7 and cooperation, benefits all the learning styles, and leads to a deeper level of learning. Surface-level learning consists of offering new concepts to students only long enough for them to regurgitate these concepts in a test a few days later.…”
Section: Importance Of Using Web 20 Toolsmentioning
confidence: 99%